Impacts of climate change and inter-annual variability on cereal crops in China from 1980 to 2008 - Zhang, Tianyi; Huang, Yao (Journal of the science of food and agriculture, 2012)
BACKGROUND: Negative climate impacts on crop yield increase pressures on food security in China. In this study, climatic impacts on cereal yields (rice, wheat and maize) were investigated by analyzing climate‐yield relationships from 1980 to 2008. RESULTS: Results indicated that warming was significant, but trends in precipitation and solar radiation were not statistically significant in most of China. In general, maize is particularly sensitive to warming. However, increase in temperature was correlated with both lower and higher yield of rice and wheat, which is inconsistent with the current view that warming results in decline in yields. Of the three cereal crops, further analysis suggested that reduction in yields with higher temperature is accompanied by lower precipitation, which mainly occurred in northern parts of China, suggesting droughts reduced yield due to lack of water resources. Similarly, a positive correlation between temperature and yield can be alternatively explained by the effect of solar radiation, mainly in the southern part of China where water resources are abundant. CONCLUSION: Overall, our study suggests that it is inter‐annual variations in precipitation and solar radiation that have driven change in cereal yields in China over the last three decades. Copyright © 2011 Society of Chemical Industry